2016
DOI: 10.1039/c6fo00223d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of equol on deoxycorticosterone acetate salt-induced hypertension and associated vascular dementia in rats

Abstract: Oxidative stress is the major cause of neuronal cell degeneration observed in neurodegenerative diseases including vascular dementia (VaD), and hypertension has been found to increase the probability of VaD. Here, we investigated the effects of equol in deoxycorticosterone acetate (DOCA)-salt-induced hypertensive rats (DHRs) and the associated VaD. The systolic blood pressure of rats treated with low- (10 mg per kg body weight) and high-dose (20 mg per kg body weight) equol for 4 weeks was lower than that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“… 42 S -Equol treatment (low-dose, 10 mg/kg and high-dose, 20 mg/kg orally for 4 weeks) could dose-dependently decrease systolic blood pressure in deoxycorticosterone acetate-salt hypertensive rats by inhibiting angiotensin-converting enzyme activity and increasing the NO production. 43 Removal of dietary soy isoflavones reduced endothelium-derived NO levels in ovariectomized rats, while S -equol supplementation (200 µg/day subcutaneously for 4 weeks starting at the 16th week after receiving an isoflavone-deficient diet) partially improved NO-mediated endothelial function. 36 In addition, S -equol treatment (0.05% and 0.1% for 12–14 weeks) displayed antiatherosclerotic properties in apolipoprotein E knockout mice fed a high-fat diet by inhibiting endoplasmic reticulum stress through the activation of nuclear factor-erythroid 2-related factor 2 in ECs.…”
Section: S -Equolmentioning
confidence: 99%
“… 42 S -Equol treatment (low-dose, 10 mg/kg and high-dose, 20 mg/kg orally for 4 weeks) could dose-dependently decrease systolic blood pressure in deoxycorticosterone acetate-salt hypertensive rats by inhibiting angiotensin-converting enzyme activity and increasing the NO production. 43 Removal of dietary soy isoflavones reduced endothelium-derived NO levels in ovariectomized rats, while S -equol supplementation (200 µg/day subcutaneously for 4 weeks starting at the 16th week after receiving an isoflavone-deficient diet) partially improved NO-mediated endothelial function. 36 In addition, S -equol treatment (0.05% and 0.1% for 12–14 weeks) displayed antiatherosclerotic properties in apolipoprotein E knockout mice fed a high-fat diet by inhibiting endoplasmic reticulum stress through the activation of nuclear factor-erythroid 2-related factor 2 in ECs.…”
Section: S -Equolmentioning
confidence: 99%
“…Antioxidant properties of S-equol are greater than vitamins C and E in in vitro studies [ 38 , 97 ]. Lie et al showed in deoxycorticosterone acetate-salt-induced hypertensive rats treated with low- (10 mg/kg/BW) and high- (20 mg/kg/BW) S-equol for 4 weeks that S-equol improved both long- and short-term memory and that S-equol increased antioxidant activity in the brain by elevating the activities of superoxide dismutase (SOD), catalase and glutathione peroxidase (GPx) levels and decreasing malondialdehyde (MDA) content and acetylcholinesterase (AChE) activity [ 98 ]. Ma et al showed in male and ovariectomized female Sprague-Dawley rats fed with S-equol (250 ppm), genistein (500 ppm), or isoflavone-reduced diet for two weeks before 90 min transient middle cerebral artery occlusion followed by reperfusion that both S-equol and genistein reduced infarct size and that S-equol and genistein reduced oxidase activity of nicotinamide adenine dinucleotide phosphate and superoxide levels in the rat brain [ 99 ].…”
Section: Potential Protective Mechanisms Of S-equol For Cognitive Dec...mentioning
confidence: 99%
“…Animal studies also demonstrated the antioxidant properties of equol. Two mice studies demonstrated that equol improved vascular health in the brain [33,105]. It was suggested that equol elevated the activities of SOD, catalase, acetylcholinesterase, and glutathione peroxidase, and decreased the MDA levels in mice that had deoxycorticosterone acetate salt-induced hypertension and associated vascular dementia [105].…”
Section: Antioxidative Effectmentioning
confidence: 99%
“…Two mice studies demonstrated that equol improved vascular health in the brain [33,105]. It was suggested that equol elevated the activities of SOD, catalase, acetylcholinesterase, and glutathione peroxidase, and decreased the MDA levels in mice that had deoxycorticosterone acetate salt-induced hypertension and associated vascular dementia [105]. Equol also reduced NADPH-induced superoxide production in the cerebral arteries of normotensive rats and hypertensive rats that were induced by angiotensin II [33].…”
Section: Antioxidative Effectmentioning
confidence: 99%